Electrospinning-assisted construction of 3D LiFePO4@rGO/carbon nanofibers as flexible cathode to boost the rate capabilities of lithium-ion batteries. Issue 1 (1st January 2023) - Liu, Jifei; Hu, Xinyi; Ran, Feitian; Wang, Kai; Dai, Jianfeng; Zhu, Xiaojun
Abstract: Rational design and construction of cathode materials with high ion transport coefficient and high electrical conductivity is of great importance for improving the reaction kinetics of Li-ion batteries (LIBs). Herein, we develop the three-dimensional (3D) LiFePO4 @reduced graphene oxide/carbon nanofibers (LiFePO4 @rGO/CNFs) to serve as flexible cathodes for LIBs. Through the electrospinning technique combined with the subsequent pyrolysis, the composite nanofiber precursors have been successfully converted into flexible electrodes. As demonstrated, the as-prepared electrodes present uniform nanofibers, in which the rGO sheets are evenly attached to CNFs, and LiFePO4 nanoparticles are homogeneously distributed in CNFs. Benefited by the structural advantages and the improving conductivity, the optimum LiFePO4 @rGO/CNFs cathode exhibits a high initial capacity of 167 mAh g −1 at 0.5 C, and maintains a reversible capacity of 150 mAh g −1 after 200 cycles at 1 C. Galvanostatic intermittent titration technique (GITT) shows that LiFePO4 @rGO/CNFs has a high ion diffusion rate (8.82 × 10 −12  cm 2  s −1 ), further suggesting that such 3D structures are appropriate as cathode materials for LIBs. These findings demonstrate that the 3D continuously conductive network of LiFePO4 composites is a promising cathode material for LIBs.